The Potential of Acalypha indica L. Leaf Extract as a Repellent Against Aedes aegypti Mosquitoes - Masruroh, Laily; -, Marlik; Nurmayanti, Demes; Pratiwi, Windri Khusuma; Wardoyo, Slamet (Sriwijaya Journal of Environment, 2024)
Number one of the issues in controlling Aedes aegypti mosquitoes is the limitations of using chemical repellents, which often have harmful side effects for humans and the environment. The solution to this problem is using natural materials, such as Acalypha indica L. This study aims to inform the results of analyzing the potential of leaf extract Acalypha indica in repelling Aedes aegypti mosquitoes. This study is experimental, using a post-test-only control group design. The subjects of the study are leaf extracts of Acalypha indica at concentrations of 10%, 15%, and 20%. The object is 2-5 days old female Aedes aegypti mosquitoes, totaling 675 individuals with 9 replications. The research variables include the number of mosquitoes landing and the protective efficacy. Data were collected through measurements and observations and analyzed using the Kruskal-Wallis test. At the 6th hour of testing, the protective efficacy for concentrations of 10%, 15%, and 20% was 75%, 70%, and 90%, respectively. Statistical analysis revealed significant differences in protective efficacy among the treatment groups (p<0.05). The concentration of 20% has proven potential in repelling Aedes aegypti mosquitoes, with 90% protective efficacy until the 6th hour of testing, according to the standards set by the Indonesian Pesticide Commission.